Vaksinasi COVID-19 ditinjau dari Perspektif Ekonomi Kesehatan - Yuliana, Yuliana (Penerbit Goodwood, 2022)
Purpose: To describe the COVID-19 vaccination from the aspects of cost-effectiveness, monetary benefit, fiscal modeling, and health efficacy. Method: It is a systematic literature review. This systematic review described COVID-19 vaccination effectiveness from health economic perspectives, cost-effectiveness, monetary benefit, fiscal modeling, and heath efficacy. Literatures were taken from PubMed and Science Direct. There were 10 papers from PubMed, 3 papers from Science Direct, and 186 from Google Scholar at the beginning. After being selected for title, abstract and full content, 11 journals were left. PRISMA guidelines were used. Inclusion criteria are review and research articles. The excluded articles that were not peer-reviewed and unavailable full-text paper. Articles were read twice to reduce the bias. The selected articles were summarized and narrated descriptively. Results: Results revealed that vaccination is cost-effective and cost-saving based on economic model analysis such as QALY rate, global COVID-19 VAR model, and ICER. The mortality and morbidity of the COVID-19 infection are depended on the vaccination program. Limitations: There were only some articles included in the systematic review. Therefore, the result might be not complete and comprehensive. Contribution: This paper can be used as a review for implementing the vaccination program based on the effectiveness from health economic perspectives.